Kesan pembangunan perindustrian di kawasan Pasir Gudang Johor terhadap tahap sosio-ekonomi penduduk perkampungan tradisional di sekitar - Ramli, Abdul Rahim (2007)
Nowadays, the development of industrial areas in our country gives many positive and negative impacts towards the environment, either directly or indirectly. This is including the traditional village areas and other settlement. Among the impacts are from the aspects of working opportunity, social change, increase in economic level and environment. Therefore, to identify and study the impacts, an empirical research had been done in the case study areas which are at Kampung Tanjung Langsat and Perigi Acheh. This is to understand the impacts from the existence of activities in Pasir Gudang Industrial Area. The research had been conducted based on secondary information and collection of primary information by interviewing and distributing questionnaires to the house leaders. Some of the respondents including the Penghulu, Ketua Kampung, Jururawat Masyarakat, Pegawai Pihak Berkuasa Tempatan Pasir Gudang (PBTPG) and local communities had been interviewed. Meanwhile, 57 house leaders in Kampung Tanjung Langsat and 50 house leaders in Kampung Perigi Acheh had been chosen using â€˜random samplingâ€™ technique. The findings showed that Pasir Gudang industrial development had given positive impacts to the local community in aspects of their income, infrastructure and public facilities. On the other hand, it also creates negative impacts such as air and water pollution and limit of area for fishing activity around the Tanjung Langsat and Perigi Acheh area. In order to minimize the negative impacts and improve both of the villageâ€™s community social economy, the research had listed several suggestions such as upgrading the infrastructure and public facilities, developing traditional villages using the approach of â€œPusat Pertumbuhan Desa (PPD)â€?, developing recreational areas and conservation of the mangrove swamp areas, and also providing early warning security system. Through the listed suggestions, it is hoped that the desire to preserve and develop those villages to be sustainable and well-equipped with public facilities, infrastructure and increase in the community socioeconomical level will become a reality.